IMPROVING STUDENTS’ READING COMPREHENSION USING LOCAL LEGEND - Nurmia, .; Apriliaswati, Rahayu; Susilowati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract The purpose of this research was to answer the problems about how does local legend improve students? reading comprehension in comprehending the detailed information, finding the meaning of words, and drawing the conclusion about moral value of narrative text to the eighth grade students of SMPN 3 Sungai Raya Bengkayang. This research was classroom action research. The data of this research were taken from the students? score and the notes were taken through observation schedule. The total number of students was 26 students. The research finding indicated that students? ability in comprehending narrative text using local legend was improved. Students? prior knowledge about local legend improved students? ability in comprehending the detailed information by asking students to arrange the random paragraph and give students testing activity, the familiarity of the words were used in local legend improved students? ability in predicting the meaning of vocabulary by asking the students to guess the meaning of the word based on the context and the environment of local culture values of local legend improved students? ability in drawing conclusion about moral value of narrative text by giving an opportunity to discuss and to conclude the lesson. It can be proven from students? mean score result in cycle 1 to cycle 3. In the first cycle, students? mean score was 48. 6, it was 64. 2 in second cycle and it raised to 78. 4 in the third cycle. Keywords: Reading Comprehension, Narrative Text, Local Legend   Abstrak Penelitian ini bertujuan untuk menjawab masalah mengenai apakah legenda  lokal meningkatkan pemahaman membaca siswa dalam memahami informasi rinci, menemukan arti kata dan menarik kesimpulan mengenai pesan moral dalam teks naratif di kelas delapan SMPN 3 Sungai Raya Bengkayang. Penelitian ini adalah penelitian tindakan kelas. Data diperoleh dari nilai siswa dan catatan observasi diperoleh melalui jadwal observasi. Jumlah siswa adalah 26. Hasil penelitian menunjukkan bahwa kemampuan siswa dalam memahami teks naratif menggunakan legenda lokal meningkat.  Pengetahuan siswa sebelumnya tentang legenda lokal meningkatkan kemampuan mereka dalam memahami informasi rinci dengan meminta siswa menyusun paragraf acak dan memberikan latihan soal, kosakata yang sudah diketahui sebelumnya yang digunakan dalam legenda lokal meningkatkan kemampuan siswa dalam memprediksi arti kosakata dengan meminta siswa menebak arti kata berdasarkan konteks, dan nilai-nilai budaya lokal di lingkungan sekitar dari legenda lokal meningkatkan kemampuan siswa dalam menarik kesimpulan pesan moral dari teks naratif dengan memberikan kesempatan untuk berdiskusi dan menyimpulkan pelajaran. Hal tersebut dibuktikan dari hasil rata-rata perolehan nilai siswa di siklus 1 hingga 3. Pada siklus pertama, rata-rata perolehan nilai siswa adalah 48. 6, 64. 2 di siklus kedua dan meningkat menjadi 78. 4 di siklus ketiga.   Kata Kunci: Pemahaman Membaca, Teks Naratif, Legenda Lokal